Morphometric Characteristic of Black Soldier Fly (Hermetia illucens) · Wuhan Strain and Its Egg Production Improved by Selectively Inbreeding - Minmin Cai; Li Li; Zhengzheng Zhao; Ke Zhang; Fang Li; Chan Yu; Rongfang Yuan; Beihai Zhou; Zhuqing Ren; Ziniu Yu; Jibin Zhang (Life, 2022)
The use of black soldier fly (BSF) larvae to recycle various organic materials while producing biomass for use as feed is well established. Variety selection is important from the perspective of application. In the current study, morphometric and life-history traits of a Wuhan-domesticated BSF colony (Wuhan strain) were compared to those of a ‘selectively inbred’ population (inbred strain, inbred for 10 generations). In terms of morphological characteristics, the results showed that both strains had dichoptic compound eyes, club-shaped antennae, blue halters, and blue-green metallic luster wings with a hexagon discal cell. In both strains, the body and wing length of female adults were slightly larger than those of male adults. The first four larval stages of the BSF occurred rapidly (1–12 days) with transitions across stages resulting in doubling of size for both populations. Selective inbreeding did not alter the life-history traits of the larval exuviate stage in terms of age, size, weight, and feed reduction rate. Overall egg production for the inbred strain was significantly higher (1.5 times greater) than the Wuhan strain. This is explained by increased adult emergence and individual oviposition performance. It was speculated that inbreeding improved the reproductive success of inbred adult female offspring and selection process steadied it. The findings indicate that selective inbreeding could enhance overall oviposition performance and provide a strategy to selectively breed BSF with high egg production for future applications.